Radical Scavenging Capacity of Rwandan CTC Tea Polyphenols Extracted Using Microwave Assisted Extraction - Nshimiyimana, Dominique Savio; He, Qian (Pakistan Journal of Nutrition, 2010)
Extracts of Cutting, Tearing and Curling (CTC) black and green teas from Rwanda were extracted using decoction and Microwave Assisted Extraction (MAE). Green Tea Extract from Microwave Assisted Extraction (GTMAE) had higher concentration of total tea polyphenols than others; (GTMAE26%>GTD21%>BTMAE16%>BTD14%). The higher the concentration of the total tea polyphenols, the higher was free radical scavenging activity. Antioxidant activity of the teas extracts is expressed by the DPPH radical scavenging with the decreased absorbance in the order: green tea microwave assisted extraction > green tea decoction > black tea microwave assisted extraction > black tea decoction extraction. Consequently, MAE method was found to much more effective than decoction in total polyphenolics content, scavenging capacity, time and energy consumption for both CTC black and green tea.